The radium girls : the dark story of America's shining women - Moore, Kate (Writer and editor) (Naperville, Illinois : Sourcebooks, Inc., 2017)
As World War I raged across the globe, hundreds of young women toiled away at the radium-dial factories, where they painted clock faces with a mysterious new substance called radium. Assured by their bosses that the luminous material was safe, the women themselves shone brightly in the dark, covered from head to toe with the glowing dust. With such a coveted job, these "shining girls" were considered the luckiest alive -- until they began to fall mysteriously ill. As the fatal poison of the radium took hold, they found themselves embroiled in one of America's biggest scandals and a groundbreaking battle for workers' rights.
List of key characters -- Prologue -- Part one. Knowledge -- Part two. Power -- Part three. Justice -- Epilogue -- Postscript.
"Originally published in 2016 in the United Kingdom by Simon & Schuster UK."--Title page verso.
Includes reading group guide (pages 409-410).
Includes bibliographical references (pages 415-467) and index.
106390
Keywords: United States Radium Corporation; Watch dial painters -- Diseases -- United States -- History; Radium paint -- Toxicology; Industrial hygiene -- United States -- History -- 20th century; Women employees -- Diseases -- United States; Consumers' leagues -- United States -- History; Employers' liability -- United States -- Case studies; World War, 1914-1918 -- Women -- United States; World War, 1914-1918 -- War work -- United States; Biography & Autobiography -- Women; History -- Military -- World War I; History -- Women; Consumers' leagues; Employers' liability; Industrial hygiene; Radium paint -- Toxicology; War work; Women; Occupational health and safety -- United States -- History; Cooperative societies -- United States -- History; Industrial painters -- Diseases -- United States -- History; Radium -- poisoning; Radiation Injuries -- history; Occupational Diseases -- history; Occupational Exposure; Women's Health; United States; Case studies; History